Time, cause of early neonatal death, and its predictors among neonates admitted to neonatal intensive care units at Bahir Dar City public hospitals, northwest Ethiopia: a prospective follow-up study - Gessesse, Abraham Dessie; Belete, Minyichil Birhanu; Tadesse, Fikir (Frontiers in Pediatrics, 2024)
Background: Globally, 75% of neonatal deaths occur during the first weeks of life and more than 43% of deaths are covered by sub-Saharan Africa. Health-related policymakers and decisionmakers need to use evidence-based treatments to reduce the time to early neonatal death and associated predictors. However, there are limited studies on median survival time, cause, incidence, and predictors in the study area as well as the country. Therefore, this study aimed to assess time, the cause of early neonatal death, and its predictors among neonates admitted to neonatal intensive care units at Bahir Dar City public hospitals in northwest Ethiopia.: An institution-based prospective follow-up study design was conducted among 387 early neonates selected by systematic sampling from February 22 to April 22, 2023. Statistical software, Epi Data version 4.6 and Stata version 14 were used for entry and analysis, respectively. Proportional hazard assumption and model fitness were checked by the Schoenfeld residual test and the Cox-Snell residual test, respectively. Descriptive statistics, the Kaplan-Meier curve, and the life table were used to describe variables. The Cox regression analysis model was fitted to identify the predictors of early neonatal death.Result: During the follow-up time, 59 (15.25%) early neonates died, with an incidence of 31.79 per 1000 early neonate days (CI 0.024, 0.041). The leading causes of early neonatal death were prematurity complications, asphyxia, sepsis, meconium aspiration syndrome, and necrotizing enterocolitis. The mean survival time was 2.72 days. Being born from a multigravida mother (AHR 4.34; CI 1.63, 11.55), a grand multigravida mother (AHR 3.50; CI 1.12, 10.95), respiratory distress syndrome (AHR 2.60; CI 1.03, 6.58), birth asphyxia (AHR 7.51; CI 2.30, 24.51), a small gestational age (AHR 2.05; CI 1.08, 4.92), and being unable to exclusively breastfeed (AHR 3.46; CI 1.52, 7.88) were significantly associated predictors for time to early neonatal death.The incidence of early neonatal death was high, and the mean survival time was 2.72 days. Gravidity, respiratory distress syndrome, birth asphyxia, and being unable to exclusively breastfeed were identified as predictors of early neonatal death. Therefore, the upcoming researcher will carry out long-term prospective follow-up studies at a multicenter, nationwide level.